Discerning experts : the practices of scientific assessment for environmental policy - Oppenheimer, Michael (Chicago : University of Chicago Press, 2019)
"Discerning Experts assesses the assessments that many governments rely on to help guide environmental policy and action. Through their close look at environmental assessments involving acid rain, ozone depletion, and sea level rise, the authors explore how experts deliberate and decide on the scientific facts about problems like climate change. They also seek to understand how the scientists involved make the judgments they do, how the organization and management of assessment activities affects those judgments, and how expertise is identified and constructed."
The need for expert judgment -- Assessing acid rain in the United States: the National Acid Precipitation Assessment Program -- Assessing ozone depletion -- Assessing the ice: sea level rise predictions from the West Antarctic Ice Sheet, 1981-2007 -- Patrolling the science/policy border -- What assessments do -- Conclusion.
Includes bibliographical references and index.
Keywords: National Acid Precipitation Assessment Program (U.S.); Environmental sciences -- Research -- Evaluation; Environmental sciences -- Research -- Evaluation -- Case studies; Acid rain -- Research -- Evaluation. -- United States; Ozone layer depletion -- Research -- Evaluation; Sea level -- Research -- Antarctica -- Evaluation; Environmental policy -- Research -- United States; Research -- Evaluation; Expertise